The value of FDG PET/CT in the management of malignant melanoma: a retrospective study - Çınar, Alev; Ince, Semra; Göker, Ülkü Nur (The European Research Journal, 2022)
Objectives: Positron Emission Tomography with Computed Tomography (PET/CT) is a valuable imaging method for the restaging of malignant diseases as well as the evaluation of treatment outcomes. Malignant melanoma is an aggressive tumor. Surgical resection is the primary treatment. As melanoma lesions are mostly FDG-avid, whole-body 18F-fluorodeoxyglucose (18F-FDG) PET/CT imaging modality can be used to determine the spread of the tumor. In the present study, we intended to share our clinical experience with FDG PET/CT in malignant melanoma patients under different kinds of treatment. Methods: In this retrospective study, the data sets of 122 patients who had surgical resection of known primary tumors, all of which were histopathology-proven malignant melanoma, were analyzed. All patients underwent baseline 18F-FDG PET/CT scan no sooner than 45 days and at least once after surgery. Clinical information, radiological imaging, histopathology, and treatment modalities were noted for all patients, and 18F-FDG PET/CT findings were examined. Results: All patients were histopathology-proven and 47 of them had acral lentiginous, 37 nodular, 23 amelanotic, and 15 atypical malignant melanoma. Local recurrence was detected by 18F-FDG PET/CT in 13 (10.6%; 3 male, 10 female) of the 122 patients, and the mean recurrence time after diagnosis was 3 ± 1.4 years. 10 patients with brain and bone metastases underwent radiotherapy. 19 patients with lung, bone, and hepatic metastases received chemotherapy and 22 patients immunotherapy. Conclusions: Malignant melanoma is a type of skin cancer that may involve any organ. In localized cases, complete surgical resection may be adequate for a cure. If diagnosed with the latter type, the whole body of the patient must be examined.